2017
DOI: 10.1111/cbdd.13085
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of naphthyl‐N‐acylhydrazone p38α MAPK inhibitors with in vivo anti‐inflammatory and anti‐TNF‐α activity

Abstract: Protein kinases constitute attractive therapeutic targets for development of new prototypes to treat different chronic diseases. Several available drugs, like tinibs, are tyrosine kinase inhibitors; meanwhile, inhibitors of serine/threonine kinases, such as mitogen-activated protein kinase (MAPK), are still trying to overcome some problems in one of the steps of clinical development to become drugs. So, here we reported the synthesis, the in vitro kinase inhibitory profile, docking studies, and the evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…2). Freitas et al (2018) 26 found similar results in theirs studies with new naphthyl-N-acylhydrazone derivatives. These authors showed high anti-inflammatory profile promoted by compound associated with low TNF-α production.…”
Section: Th2 Cytokines and Low Nitric Oxide Production Promoted By Compound 3b In Mice Splenocytes Culturessupporting
confidence: 53%
“…2). Freitas et al (2018) 26 found similar results in theirs studies with new naphthyl-N-acylhydrazone derivatives. These authors showed high anti-inflammatory profile promoted by compound associated with low TNF-α production.…”
Section: Th2 Cytokines and Low Nitric Oxide Production Promoted By Compound 3b In Mice Splenocytes Culturessupporting
confidence: 53%
“…Mechanistic investigations showed the ability of our degraders to work through a mechanism similar to other PROTACs (Figure ) with a DC 50 in the low nanomolar range and almost complete degradation within 6 h (Figure ), making it a valuable chemical probe for ERα. Although the acylhydrazone moiety has been identified in various bioactive compounds, including compounds with in vivo activity, , it is well-known that hydrolysis can occur under acidic conditions. In order to increase the stability and drug-likeness of the degraders, we modified the linkage to an amide containing the same number of atoms within the linker in the second stage and confirmed that the biological activity was retained (Figures and ).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of this compound to inhibit other kinases, as off-targets, was not described by the authors. [51] Tariq et al (2018) synthesized a new series of N-[3-(substituted-4H-1,2,4-triazol-4-yl)]-benzo[d]thiazol-2-amines (4 a-n) and subjected to in vitro evaluation for anti-inflammatory activity and p38α MAPK inhibition. Compound 4 f, which has a type I mode of inhibition, was found to be the most active with an IC50 of 0.036 � 0.12 μM and showed the maximum anti-inflammatory activity when compared to the standard drug diclofenac sodium.…”
Section: P38 Mapk Inhibitors In Vitro Studiesmentioning
confidence: 99%